Analysis of the Content of Published Articles in the Journal Sport Mont in 2006 - Marina Vukotic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
The Montenegrin Sports Academy organized in 2006, the Second Congress and the Third Scientific Conference, with the international editorial and reputation, published by Sport Mont, 4(10-11). In this issue of the magazine there are 103 scientific papers from different multidisciplinary and monodisciplinary fields. The papers are classified by sports disciplines: training and testing, of multidisciplinary impact, kinematics, physiology of sport, sports history, sports sciences, sports psychology, sports medicine, sports management, sports equipment and technology, physical education and methodology, sports recreation, corrective gymnastics and anthropometry. In this paper we classified works by field, method of addressing analysis and found that the most numerous works from training and testing and multidisciplinary influence. We found that the published works had different themes of different multidisciplinary and monodisciplinary areas. Cited works can also be useful for further theoretical research, as they indicate the summing up of experiences and pointing to professional-scientific knowledge of practice and theory, and thus a wider view of the vital issues of sport, and of its overall achievements within the most current scientific fields.